Cretaceous provenance change in the Hegang Basin and its connection with the Songliao Basin, NE China: Evidence for lithospheric extension driven by palaeo-Pacific roll-back - Sun, M.; Chen, H.; Zhang, F.; Wilde, Simon; Minna, A.; Lin, X.; Yang, S. (Geological Society of London, 2014)
The Cretaceous Hegang Basin is located on the Jiamusi Block, NE China, and separated from the Songliao Basin by the Lesser Xing'an Range (LXR). Seismic interpretation shows that the Chengzihe, Muling and Dongshan formations of the Hegang Basin thicken eastwards with westwards onlap, indicating that the LXR existed as a palaeo-uplift during that period, whereas the Houshigou Formation shows no thickness change, indicating that the LXR was possibly under water at this time. This is supported by results of detrital zircon analysis from the Hegang Basin in which the Chengzihe Formation is dominated by approximately 180 Ma zircons, which can only be provided by the LXR, whereas the Houshigou Formation records no Early Jurassic ages. This view is consistent with previous studies of the Songliao Basin for a provenance change between the Denglouku and Quantou formations. We conclude that the LXR was a highland during deposition of the Chengzihe, Muling and Dongshan formations but that it was under water when the Houshigou Formation was deposited. There was thus a connection between the Hegang and Songliao basins, which marks an eastwards migration of the depositional and extensional centre of the Songliao-Hegang basin system. This eastwards migration implies lithospheric extension driven by palaeo-Pacific roll-back.